Pulsed field ablation of superior vena cava in paroxysmal atrial fibrillation: a case report - Tao, Yirao; Zhou, Yang; Sun, Xuerong; Liao, Wenkai; Wang, Yanjiang; Shi, Liang; Liu, Xingpeng (Frontiers in Cardiovascular Medicine, 2023)
Paroxysmal atrial fibrillation originates most commonly in the pulmonary veins. However, the superior vena cava has proved to be arrhythmogenic in some cases. Pulsed field ablation, an emerging ablation technology, selectively affects myocardial tissue. Herein, we present a case of paroxysmal atrial fibrillation in a 64-year-old man who was admitted to our hospital for pulsed field ablation. The tachycardia was recurrent despite four successful pulmonary vein isolations. The superior vena cava was determined to be involved in arrhythmogenesis. The atrial fibrillation terminated immediately after the pulsed field ablation discharge at the superior vena cava.